Didattica a distanza in contesti di emergenza: le criticità messe in luce dalla ricerca - Capperucci, Davide (Studi sulla Formazione/Open Journal of Education, 2021)
This paper investigates the strengths and weaknesses of distance learning at the time of Covid-19 starting from the contribution provided by empirical research in education, with particular reference to the results of the national research conducted by SIRD (Italian Educational Research Society) on this issue during the lock down period.